One-pot catalytic enantioselective synthesis of 2-pyrazolines - Thomson, C; Barber, D; Dixon, D (Wiley, 2019)
A scalable, one-pot, enantioselective catalytic synthesis of 2-pyrazolines from beta-substituted enones and hydrazines is described. Pivoting on a two-stage catalytic Michael addition/condensation strategy, the use of an aldehyde to generate a suitable hydrazone derivative of the hydrazine was found to be key for curtailing background reactivity and tuning the catalyst-controlled enantioselectivity. The new synthetic method is easy to perform, uses a new and readily prepared cinchona-derived bifunctional catalyst, is broad in scope, and tolerates a range of functionalities with high enantioselectivity (up to >99:1 e.r.). The significant scalability of this methodology was demonstrated with the synthesis of more than 80 grams of a pyrazoline product with 89 % catalyst recovery.